A novel octopamine receptor with preferential expression in Drosophila mushroom bodies. - Han, K.A.; Millar, N.S.; Davis, R.L. (Journal of Neuroscience, 1998)
Octopamine is a neuromodulator that mediates diverse physiological processes in invertebrates. In some insects, such as honeybees and fruit flies, octopamine has been shown to be a major stimulator of adenylyl cyclase and to function in associative learning. To identify an octopamine receptor mediating this function in Drosophila, putative biogenic amine receptors were cloned by a novel procedure using PCR and single-strand conformation polymorphism. One new receptor, octopamine receptor in mushroom bodies (OAMB), was identified as an octopamine receptor because human and Drosophila cell lines expressing OAMB showed increased cAMP and intracellular Ca2+ levels after octopamine application. Immunohistochemical analysis using an antibody made to the receptor revealed highly enriched expression in the mushroom body neuropil and the ellipsoid body of central complex, brain areas known to be crucial for olfactory learning and motor control, respectively. The preferential expression of OAMB in mushroom bodies and its capacity to produce cAMP accumulation suggest an important role in synaptic modulation underlying behavioral plasticity.